IDENTIFIKASI KESULITAN BELAJAR PESERTA DIDIK PADA MATERI KESETIMBANGAN ION DAN pH LARUTAN GARAM DI KELAS XI MIPA SMAN 1 KUANTAN MUDIK - Andorlan, Ringga; Rery, R. Usman; Azmi, Johni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the difficulties and factors that cause learning difficulties of students on the ion balance and pH of salt solution in class XI MIPA 3 SMAN 1 Kuantan Mudik. This research is a descriptive study with a qualitative case study approach, the population of class XI with a sample size of 35 people in class XI MIPA 3. The data collection technique uses the technique of test questions and questionnaires, and interviews, while the data collection tools use test questions and questionnaire sheets. The results showed that the students had difficulty learning in determining the pH of the salt solution with high and very high categories of learning difficulties. Internal factors that affect students 'learning difficulties are motivational aspects with indicators of learning efforts about ionic balance and pH of salt solution and students' attention to learning these materials with percentage effects of 59.28% and 57.85%, respectively, while external factors which affects learning difficulties in the aspects of teacher teaching 59.86% respectively. The conclusion of this study is that there are learning difficulties of students on the matter of ionic equilibrium and the pH of the salt solution and there are both internal and external factors that affect the learning abilities of students.Key Words: Analysis, Ionic Equilibrium and pH of Saline Solution, Learning Difficulties for